ANALISIS KEEFEKTIFAN PENGGUNAAN SISTEM INFORMASI MANAJEMEN PADA BISNIS UMKM - Adila, Cut Wina; Aprilianty, Ajeng Putri; Nurhasanah, Vina (Transpublika Publisher, 2022)
Management Information System is a computer-based system that provides information to consumers with common demands. SIM card users are typically official organizations, corporations, or subsidiary units. MIS data describes the company or one of the most effective techniques in terms of what has occurred in the past, what is occurring at present, and what may occur in the future. Micro and small businesses in Indonesia have demonstrated their potential to keep the economy afloat in times of crisis. Additionally, 99.99 percent of all businesses in Indonesia are held by small and medium-sized enterprises (SMEs), which employ 97.30 percent of the population of Indonesia. In addition, 57.12 percent of the GDP is contributed by MSMEs. The operation of a firm can be challenging for small and medium-sized businesses (SMEs). Small business funding is a serious concern. Poor management, swift competition, a lack of innovation in MSMEs, unfavorable government rules for MSMEs, challenges in acquiring raw materials, and rapid changes in consumer tastes that lead to marketing are some other issues. It is expected that the government will play a significant role in resolving these hurdles. The government is mandated by law to assist and support small enterprises. The central government and local governments must collaborate to encourage the development of small and medium enterprises (SMEs).